A new genus for a colorful spirostreptid milliped from East Africa (Diplopoda: Spirostreptida: Spirostreptidae) - Hoffman, Richard L.; Enghoff, Henrik (Zootaxa, 2011)
The new generic taxon Sagmatostreptus is proposed for the type species Spirostreptus strongylopygus Attems, 1950, endemic to a limited area in northeastern Tanzania and adjacent Kenya.